The optimal diagnostic criteria of endogenous hyperinsulinemic hypoglycemia based on a large cohort of Chinese patients - Yu, Jie; Liu, Yiwen; Lyu, Lu; Zhao, Yuan; Qi, Mengya; Ping, Fan; Xu, Lingling; Li, Wei; Xu, Qiang; Zhang, Huabing; Wu, Wenming; Li, Yuxiu (Frontiers in Endocrinology, 2022)
Abstract Purpose: An end-of-fast insulin level ≥ 3 µIU/ml, C-peptide level ≥ 0.6 ng/ml, and proinsulin level ≥ 5 pmol/l with end-of-fast glucose level ≤ 3.0 mmol/l have been established as the criteria for endogenous hyperinsulinemic hypoglycemia. However, all these criteria have been proposed for patients in Western populations. This study aimed to determine the optimal criteria for Chinese populations using a large series of Chinese patients. Methods: This retrospective study comprised 166 patients with surgically proven insulinoma and 53 controls who underwent a 72-h fasting test at the Peking Union Medical College Hospital(PUMCH) from 2000 to 2020. Receiver operating characteristic curves were used for analysis. Results: In this series of patients, the optimal diagnostic criteria for endogenous hyperinsulinemic hypoglycemia were insulin  ≥ 5.5 μIU/ml, C-peptide ≥ 0.7 ng/ml, and proinsulin ≥ 12 pmol/l with end-of-fast glucose ≤ 2.8 mmol/l; the sensitivity and specificity were 99% and 100% for insulin, 100% and 100% for C-peptide, and 93% and 100% for proinsulin, respectively. The diagnostic efficacy of the criteria for Western populations was then tested. The sensitivity and specificity of end-of-fast insulin ≥ 3 μIU/ml, C-peptide ≥ 0.6 ng/ml, and proinsulin ≥ 5 pmol/l with end-of-fast glucose ≤ 3.0 mmol/l were 100% and 83%, 100% and 80%, and 97% and 78%, respectively. Conclusions: New and optimized diagnostic criteria for endogenous hyperinsulinemic hypoglycemia in Chinese populations have been proposed, and these criteria yield satisfactory accuracy.